Bibliometric analysis: a study of the chronic atrophic gastritis in gastric cancer (2015–2024) - Xu-Li Liu; Li-Li Li; Ji-Lan Wan; Li-Qian Chen; Mai-Qing Yang (Frontiers in Oncology)
ObjectiveGastric cancer (GC) is common worldwide and the fifth leading cause of cancer-related deaths. Chronic atrophic gastritis (CAG) is a precancerous stomach lesion closely associated with GC. This study aimed to conduct a comprehensive analysis of global CAG research in GC and provide a knowledge framework from a holistic and systematic perspective based on bibliometric analysis.MethodsStudies focusing on CAG in GC were performed using the Web of Science Core Collection database. The annual output, cooperation, hotspots, research status, and development trends in this field were analyzed using bibliometric software (VOSviewer and CiteSpace).ResultsA total of 1,065 articles published between 2015 and 2024 were selected. Recently, the number of publications and citations has increased. Cooperation network analysis indicated that China holds the foremost position in the research on CAG in GC, with the highest volume of publications and citations, thus exerting the greatest influence. China Medical University had the highest research output. Additionally, World Journal of Gastroenterology has reported the highest degree of productivity in this field. Yuan Yuan was the top contributor and the most frequently co-cited author. Cluster analysis of the authors’ keywords identified four key areas: Helicobacter pylori, atrophic gastritis, dysplasia, biomarkers and artificial intelligence, which have attracted increasing attention from researchers.DiscussionThis bibliometric analysis provides a data-based and objective introduction to CAG in GC and offers readers a valuable reference for future research.ConclusionsOur study systematically summarizes the results of CGA in GC research (2015–2024) and describes and predicts research hotspots and trends on a global scale. Mechanisms and therapies of CAG in GC remain key future research topics.